Controllable synthesis of hollow microspheres with Fe@Carbon dual-shells for broad bandwidth microwave absorption. (June 2019) - Li, Xiao-Peng; Deng, Zhiming; Li, Yue; Zhang, Hao-Bin; Zhao, Sai; Zhang, Yu; Wu, Xin-Yu; Yu, Zhong-Zhen
Abstract: Lightweight and high-performance microwave absorption materials with satisfactory absorption capability over broad frequency ranges are urgently required for electronic, aerospace and defense applications. Herein, an efficient and scalable approach is designed for synthesizing dual-shelled and hollow Fe@C microspheres by coating a ferric precursor on sulfonated polystyrene (PS) microspheres in a buffer solution and a thin layer of polydopamine (PDA) followed by annealing at 600 °C to decompose the internal PS cores and carbonize the external PDA shell. The resulting amorphous carbon shell ensures the formation of metallic Fe by a carbothermal reaction and stabilizes the hollow and spherical architecture. The generated Fe nanoparticles and the carbon layers combine the magnetic and dielectric losses together, improving the impedance matching and thus enhancing the microwave absorption performances over a broad frequency range. The minimum reflection loss of the hollow microspheres is as low as −54.4 dB at 8.8 GHz at a thickness of 4.5 mm and its effective absorption bandwidth is as broad as 8.1 GHz at a thickness of 3 mm, covering the entire X-band frequency range. This work provides an efficient and scalable approach for fabricating dual-shelled and hollow-structured Fe@C microspheres as lightweight and highly efficient microwave absorbers. Graphical abstract: Image 1